Salicylic Acid effectiveness as Resistance Inducer of Rice Plant Against Sheath Blight Pathogen - Suharti, Woro Sri (Agrotechbiz : Jurnal Ilmiah Pertanian, 2023)
This study aims to determine the effectiveness of salicylic acid in inhibiting the growth of Rhizoctonia solani in vitro and to determine the effect of salicylic acid in increasing rice plants' resistance to rice sheath blight disease. In the in vitro research stage, the antifungal activity of salicylic acid was assayed with 5 levels of concentration. The observed variable was the percentage of R. solani mycelium growth inhibition. The next stage of research was carried out in planta. The observed variables in the resistance assay were the pathosystem, growth, morphological, and physiological components. Based on the observed variables of pathosystem components, salicylic acid can reduce the intensity of rice sheath blight both in vitro and in planta. Based on observations of morphological and physiological components, the salicylic acid increased plant resistance by thickening the leaf epidermis and increasing the phenolic compounds.